Analysis of School Promotion Program in Admission of New Learners at SMP IT Raudhatur Rahma Pekanbaru - Rita Andriani; Fadly Azhar; Azhar Azhar (FKIP - Universitas Riau, 2026)
This research was motivated by the phenomenon of a significant decrease in the number of new students at SMP IT Raudhatur Rahma Pekanbaru in the last three years, which ultimately led to the school not opening the New Student Admission (PPDB) in 2024. The purpose of this study is to analyze the implementation of promotional programs in PPDB at SMP IT Raudhatur Rahma, examine the types of promotions used, and identify the obstacles faced in its implementation. This research used a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the school has implemented a promotional strategy by referring to the marketing mix principles (7P), AIDA model, STP, and Promotion Mix components. The promotional strategies used include distributing brochures, direct visits to elementary schools, using social media, and providing incentives such as discounts and vouchers. However, the implementation of promotion has not run optimally due to several obstacles, including: the absence of a special promotion team, the limited utilization of digital media, and the lack of physical facilities that affect the school's image.